ANALISIS PENGARUH PENGAWASAN FUNGSIONAL, AKUNTABILITAS PUBLIK, TRANSPARANSI DAN PENINGKATAN PELAYANAN PUBLIK TERHADAP KINERJA PEMERINTAH DAERAH - Jumirin Asyikin; Ismiati (Jurnal Kajian Akuntansi dan Auditing, 2021)
This study aims to empirically test the functional supervision, public accountability, transparency and improvement of public services that affect the dependent variable of local government performance at the PUPR Office of Batola Regency, either partially or simultaneously. The design in this study is a quantitative comparative causal research. The population in this study were all employees at the PUPR Office of Batola Regency using purposive sampling method. Data collection techniques used through questionnaires. Testing the research hypothesis using multiple regression analysis. The results of this study indicate that partially functional supervision has a positive and significant effect on local government performance. For public accountability does not affect the performance of local governments with a negative direction of influence. Transparency also has no effect on local government performance and has a positive direction of influence. And to improve public services has a positive and significant effect on the performance of local governments. Keywords: functional supervision, public accountability, transparency, improvement of public services and local government performance